Assessing suitability of parts for additive manufacturing. (2022) - Zhen Yong, Yeo; Cardeal, Gonçalo; Silva, Arlindo; Ribeiro, Inês; Leite, Marco
Abstract: With the improvement to additive manufacturing (AM) technologies as well as an increasing emphasis on strengthening the global logistic chain, there has been growing interest in introducing AM for spare parts production, to increase resilience against supply disruptions. Therefore, guidelines and frameworks for aiding companies determining the suitability of spare parts for additive manufacturing have become more relevant. In a previous paper [1], the authors proposed a method for exploring the suitability of this framework for obsolete parts, where a 2-stage sequence is proposed to assist new companies deciding parts for AM. The first stage ranks and identifies potential feasible parts, mainly on potential inventory savings. The second stage focuses on a user dependent weighted matrix, to align any potential goals of the company. This paper aims to expand on the possibility of utilizing this framework, for non-obsolete parts, through the analysis of a case study involving multiple parts. Results are analyzed and possible limitations are presented and discussed in the context of non-obsolete spare parts.